Sobre el status gramatical del aspecto y sus relaciones con las propiedades temporales y accionales - Nowikow, Wiaczesław (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
The aim of this paper is to present the following three questions: a) the grammatical status of the Aspect; b) the relations of this category to temporal properties (Tense); c) the relations of the Aspect to actional properties (Aktionsart). The author makes a typological-comparative analysis of the above-mentioned categories and relations in the modern Spanih and Polish and explains the differences and coincidences between these languages in the matter of the temporality and aspectuality.
About grammatical status of the aspect and its relations to temporal and actional properties